Efficacy and safety of early aspirin withdrawal and continuation of ticagrelor monotherapy post PCI for STEMI. A post hoc analysis of the randomized global leaders trial. (14th October 2021) - Gamal Setih, A; Hara, H; Tomaniak, M; Lunardi, M; Gao, C; Ono, M; Kawashima, H; Juni, P; Vranckx, P; Windecker, S; Hamm, C; Gabriel Steg, P; et al.
Abstract: Background: Clinical presentation with STEMI is considered as a highly prothrombotic condition often associated with recurrent ischemic events. The role of aspirin as part of antiplatelet regimens in STEMI patients needs to be clarified especially in the context of new potent P2Y12 inhibitors Aim: To assess the benefit and risk of 23-month ticagrelor monotherapy after one month of DAPT against the conventional 12-month DAPT with aspirin and ticagrelor followed by aspirin monotherapy among STEMI patients in the GLOBAL LEADERS trial. Methods: We did a post hoc analysis of STEMI patients in the GLOBAL LEADERS trial (2092 patients). We compared the experimental ticagrelor monotherapy group (1062 patients) with the standard 12-month DAPT group (1030 patients) in rates of GLOBAL LEADERS predefined primary (composite of all-cause mortality or non-fatal, new Q-wave myocardial infarction (MI) and secondary end points (BARC 3 or 5 bleeding). NACE (Net Adverse Clinical Events) and POCE (Patient- Oriented Composite End points). We also compared GLOBAL LEADERS predefined end points in STEMI, UA, NSTEMI and CCS in both treatment arms. Results: At two years, there were no significant differences in rates of GLOBAL LEADERS primary end points in patients who had or did not have STEMI. BARC bleeding in either treatment group didn't vary significantly among STEMI, NSTEMI and UA. Nevertheless, the experimental strategy had led to significant increase in BARC bleeding in CCS compared with STEMI at 1 and 2 years. There were similar rates of NACE and POCE in both the experimental and reference treatment groups at 1 and 2 years post PCI. Conclusions and relevance: The incidence of GLOBAL LEADRER defined end points has not been impacted by STEMI presentation. Our findings suggest that an earlier cessation of DAPT at 1 month post primary PCI, with continuation of a potent P2Y12 antagonist monotherapy, could be safe and avoids additional bleeding risk in the STEMI setting. Given the post-hoc nature of the analysis, our findings should not necessitate changes in recommendations for practice by professional associations and regulatory agencies. However, all reported findings should rather be considered only as hypothesis-generating and need be replicated in dedicated large-scale randomized trials to further assess the role of Aspirin free antithrombotic strategies post PCI in STEMI. FUNDunding Acknowledgement: Type of funding sources: None.